2021
DOI: 10.3389/fonc.2021.779042
|View full text |Cite
|
Sign up to set email alerts
|

PCNA in Cervical Intraepithelial Neoplasia and Cervical Cancer: An Interaction Network Analysis of Differentially Expressed Genes

Abstract: The investigation of differentially expressed genes (DEGs) and their interactome could provide valuable insights for the development of markers to optimize cervical intraepithelial neoplasia (CIN) screening and treatment. This study investigated patients with cervical disease to identify gene markers whose dysregulated expression and protein interaction interface were linked with CIN and cervical cancer (CC). Literature search of microarray datasets containing cervical epithelial samples was conducted in Gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The FIGO staging system has also been characterized as the most reliable prognostic factor for primary MM of the cervix by Min et al [ 9 ]. Cervical MM is considered to be human papillomavirus (HPV)-independent and distinct compared to other cervical epithelial malignancies [ 109 , 110 , 111 , 112 ], based on findings from matched controlled studies that examined the presence of different HPV subtypes in patients with malignant melanomas [ 113 ]. While the co-existence of cervical MM with other histological types of cervical cancer is pathophysiologically possible, it is rare based on the currently available literature.…”
Section: Discussionmentioning
confidence: 99%
“…The FIGO staging system has also been characterized as the most reliable prognostic factor for primary MM of the cervix by Min et al [ 9 ]. Cervical MM is considered to be human papillomavirus (HPV)-independent and distinct compared to other cervical epithelial malignancies [ 109 , 110 , 111 , 112 ], based on findings from matched controlled studies that examined the presence of different HPV subtypes in patients with malignant melanomas [ 113 ]. While the co-existence of cervical MM with other histological types of cervical cancer is pathophysiologically possible, it is rare based on the currently available literature.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that early surgical resection of NSCLC can increase the 5-year survival by up to 70%; unfortunately, almost 75% of cases are detected at the time of advanced disease (Stages III/IV), making it difficult to manage the disease despite significant modern advancements in oncology practice [ 51 ]. Furthermore, past works have identified various diagnostic and prognostic signatures in cancers for patient stratification using gene expression and omics data; however, this approach has failed to capture the synergistic effects of gene expression [ 17 , 18 , 19 ]. Therefore, applying AI and MLT to omics data could be a promising approach for identifying and developing better prognostic and diagnostic models in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic markers might be helpful for evaluating treatment outcomes and monitoring and selecting suitable therapeutic strategies in NSCLC [ 17 ]. Integrated bioinformatic analysis of differentially expressed genes was successfully used to identify the potential prognostic gene signatures in other cancers, including esophageal squamous cell carcinoma and cervical cancer [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Central gene elements of the aging rat hippocampal network were inferred by measuring network features from their complex interactome and by identifying sub-networks and hub objects ( Giannos et al, 2021a , b , 2022 ). Highly clustered DEGs or densely connected modules in the PPI network were identified using the molecular complex detection ( Bader and Hogue, 2003 ).…”
Section: Methodsmentioning
confidence: 99%